2019
DOI: 10.1103/physrevb.100.035123
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of lattice fractional quantum Hall Hamiltonians derived from conformal field theory

Abstract: Conformal field theory has recently been applied to derive few-body Hamiltonians whose ground states are lattice versions of fractional quantum Hall states. The exact lattice models involve interactions over long distances, which is difficult to realize in experiments. It seems, however, that such long-range interactions should not be necessary, as the correlations decay exponentially in the bulk. This poses the question, whether the Hamiltonians can be truncated to contain only local interactions without chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Continuum FQH states in the Jain hierarchy (ν = 1/3, 2/5, 3/7,...) have been shown numerically [1,2,23], and for the Laughlin state also experimentally [24,25], to possess Abelian topological order for the Coulomb interaction. The analysis of corresponding lattice FQH states, on the other hand, is complicated by several factors, including the limited number of viable experimental systems [15] and the difficulty of engineering long-range interactions [26]. Coupled with this, it has been shown that the lattice can host fundamentally different phases of matter [27], as well as states with non-Abelian statistics at equivalent filling factors [13,28].…”
Section: Introductionmentioning
confidence: 99%
“…Continuum FQH states in the Jain hierarchy (ν = 1/3, 2/5, 3/7,...) have been shown numerically [1,2,23], and for the Laughlin state also experimentally [24,25], to possess Abelian topological order for the Coulomb interaction. The analysis of corresponding lattice FQH states, on the other hand, is complicated by several factors, including the limited number of viable experimental systems [15] and the difficulty of engineering long-range interactions [26]. Coupled with this, it has been shown that the lattice can host fundamentally different phases of matter [27], as well as states with non-Abelian statistics at equivalent filling factors [13,28].…”
Section: Introductionmentioning
confidence: 99%
“…We would like to split this Hamiltonian into a noninteracting part plus interactions. By multiplying out the terms in the defining Hamiltonian, one obtains [38]…”
Section: B Decomposition Into One-body Two-body and Three-body Partsmentioning
confidence: 99%
“…Following Ref. [38], we present and use the Hamiltonians in a form that distinguishes one-body, two-body, and three-body terms. In Sec.…”
Section: Introductionmentioning
confidence: 99%
“…[44], and studied further in [48]. Moreover, a general procedure of truncating the long-range terms was formulated for Hamiltonians constructed from conformal field theory [49]. While so far it was applied only to the parent Hamiltonians of Abelian states, the longrange Hamiltonian from Ref.…”
Section: Introductionmentioning
confidence: 99%